2011
DOI: 10.1158/0008-5472.can-10-4076
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Targeting of Tumor Antigens Expressed by Cancer Vaccines Can Improve Antigen Immunogenicity and Therapeutic Efficacy

Abstract: MVA-BN-PRO (BN ImmunoTherapeutics) is a candidate immunotherapy product for the treatment of prostate cancer. It encodes 2 tumor-associated antigens, prostate-specific antigen (PSA), and prostatic acid phosphatase (PAP), and is derived from the highly attenuated modified vaccinia Ankara (MVA) virus stock known as MVA-BN. Past work has shown that the immunogenicity of antigens can be improved by targeting their localization to exosomes, which are small, 50-to 100-nm diameter vesicles secreted by most cell types. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 16 publications
1
104
0
1
Order By: Relevance
“…The heat treatment leads to increased exposure of MHC class I molecules, chemokines, and HSPs, the last of these acting as molecular chaperones having potent adjuvant activity in the induction of antigen-specific T-cell responses and therefore increased immunogenicity (Dai et al, 2005;Chen et al, 2006Chen et al, , 2011. Other protocols include administration of the exosomes after pretreatment with immune-potentiating doses of cyclophosphamide (Taieb et al, 2006), priming of DCs with exosomes from genetically modified tumor cells expressing interleukin-2 or interleukin-12 , or overexpression of fusion proteins consisting of tumor-associated antigens and the C1C2 domain of lactadherin (Hartman et al, 2011;Rountree et al, 2011). Furthermore, exosomes from mature DCs are more efficient in eradicating established tumors than exosomes from immature DCs in vivo, because exosomes from mature DCs express higher levels of MHC complexes and T-cell costimulatory molecules (Hao et al, 2007).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The heat treatment leads to increased exposure of MHC class I molecules, chemokines, and HSPs, the last of these acting as molecular chaperones having potent adjuvant activity in the induction of antigen-specific T-cell responses and therefore increased immunogenicity (Dai et al, 2005;Chen et al, 2006Chen et al, , 2011. Other protocols include administration of the exosomes after pretreatment with immune-potentiating doses of cyclophosphamide (Taieb et al, 2006), priming of DCs with exosomes from genetically modified tumor cells expressing interleukin-2 or interleukin-12 , or overexpression of fusion proteins consisting of tumor-associated antigens and the C1C2 domain of lactadherin (Hartman et al, 2011;Rountree et al, 2011). Furthermore, exosomes from mature DCs are more efficient in eradicating established tumors than exosomes from immature DCs in vivo, because exosomes from mature DCs express higher levels of MHC complexes and T-cell costimulatory molecules (Hao et al, 2007).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…57 The antitumor potential of this approach was also demonstrated in two prostate cancer models, in which tumor growth was severely attenuated by vaccination with exosomes displaying the tumor antigens, prostate-specific antigen or prostatic acid phosphatase. 58 The feasibility of antitumor therapy based on immunostimulatory exosomes was evaluated in two Phase I trials. 59,60 In these trials, dendritic cells of patients with stage III/IV melanoma were isolated and pulsed with MAGE3 tumor antigens.…”
Section: Exosome-based Drug Delivery Systems: Biotechnological Versusmentioning
confidence: 99%
“…[56][57][58] In such strategies, the phosphatidylserine-binding domain of the opsonin is used to coat exosomes and exploit the excellent delivery potential of these vesicles to deliver the antigen to antigen-presenting cells, resulting in immune responses. These studies illustrate the versatility of the lactadherin protein and its application in exosome mimetic-mediated drug delivery.…”
mentioning
confidence: 99%
“…Types of tumor cells such as ovarian cancer, chronic myelogenous leukemia were demonstrated to secret functional exosomes (Cho et al, 2011;Clayton et al, 2011;Hood et al, 2011;Taverna et al, 2012). Studies have reported that the exosomes implicated in the cell-to-cell signaling (Lotvall et al, 2007), involve in presentation of Ags to T cells in the immune system (Prado et al, 2008) and the exosomes from tumor cells promote the immune response to tumors by presentation of tumor Ags (Rountree et al, 2011). However, it has also been reported that exosomes from murine mammary tumor cells including TS/A and 4T1 cells can inhibit NK cells cytolytic activity by down-regulation of the expression of perforin, exosomes from breast tumors inhibit the activation of T cells (Liu et al, 2006).…”
Section: Exosomes From Murine-derived Gl26 Cells Promote Glioblastomamentioning
confidence: 99%